Conflict Sensitivity in Development: A Study On Proposed Arial Beel International Airport Project In Bangladesh (Social Science Review, 2023)
This paper has dual objectives: to understand the importance of conflict sensitivity in development and to examine the relevance of conflict sensitivity in practical terms through a case study—the proposed Arial Beel International Airport Project. Written, based on secondary resources available in books, journal articles, and online sources, it argues that conflictsensitive approaches to development pay attention to contextual realities to avoid any intentional and unintentional ‘harm’ that a context may face due to insensitive developmental intervention. On the Arial Beel case, it found that a localised, violent resistance movement developed against the decision to construct a modern airport due to inadequate attention to local realities and inappropriate pre-project development assessment processes. The government had to backtrack the project. However, at the latter stage, the decision-makers learned to respect local sensitivities while looking for alternative sites for an airport project. It suggests an insensitive development project that becomes unwanted too to locals could influence policymakers to learn about contextual sensitivities and respect the pulse of people on the ground.Social Science Review, Vol. 39(2), June 2022 [Special Issue] Page 19-37